An experimental study of the effects of negative, capped and deferred bonuses on risk taking in a multi-period setting - Hartmann, Frank; Slapničar, Sergeja (Journal of management and governance, 2015)
As a response to the financial crisis in 2008, the European bank authorities have adopted new rules for managerial remuneration. These rules are intended to mitigate managerial propensity to excessive risk taking. The purpose of this paper is to examine three prominent recommendations in these remuneration rules: the use of negative bonuses, the use of bonus caps and the use of deferred bonus payment. The paper advances the theory that cognitive frames created by compensation design affect risk-taking behaviour. We conduct a two-by-two within-subject experiment in which 153 students are set an investment task involving two periods. We find higher risk taking with the high variance bonus scheme that contains a negative bonus option. While bonus deferral appears to have no such initial effect on risk taking, it affects risk behaviour in the second period as a response to positive and negative outcomes from the first period. The findings contribute to the theory and practice of bonus system design and the application of contemporary remuneration recommendations in the financial sector.